STRATEGI INOVASI PERTANIAN SEBAGAI UPAYA MEWUJUDKAN KETAHANAN PANGAN - Supraptha, I Gede Chaitanya Indra; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Batu is a city located in East Java, Indonesia. This city is located fifteen kilometers northwest of Malang and about ninety kilometers southwest of Surabaya. Batu is famous as an agricultural area in East Java that produce flowers, apples, and vegetables. According to the Statistics Indonesia of Batu City, the agricultural products of the city reached 2996 tons in 2021, and the consumption of its citizens was higher, i.e., 22,845 tons. These figures indicate gaps in the food resilience of the city, which encourage efforts to enhance the said resilience. Using the data acquired from interviews, observations, and documentations, this descriptive research conducted qualitative analysis using case study approach and finds that agriculture in Bati City is more advanced than its horticultural agriculture, thanks to the existing technological advancement. Gaps were found in the production of non-horticultural crops, i.e., rice. In the overall, innovation and technology in Batu City is highly developed. Therefore, this research recommends the development of sustainable innovation and technology, the reinforcement of institutional roles, and the preservation and creation of policies regarding price stability.